A Secure Anonymous Identity-Based Virtual-Space Agreement Method for Crowds-Based Anonymous Communicate Scheme - Kai Lin; Kaiyu Wang; Jin Shang; Qindong Sun (IET Information Security)
Anonymous data exchange is in great demand in many situations, especially in remote control systems, in which a stable, secure, and secret data channel must be established between the controlling and controlled parties to distribute control commands and return data. In the previous work, we built a two-level Virtual-Space anonymous communication scheme based on the Crowds System for performing secret data exchange in remote control systems. However, as an essential part of security and anonymity, participating nodes’ identity declaration and session key agreement phases were not well designed. In this paper, we redesign the identity agreement and declaration process and design an identity-based Virtual-Space agreement method using the extended Chebyshev Chaotic Maps. In this approach, we transform the identity declaration process into a multilevel Virtual-Space agreement problem, where a series of security-progressive Virtual-Space addresses are negotiated between the controller and the controlled nodes. The protocol can handle the case where there are multiple controllers in the system, and the negotiated Virtual-Space depends on the identity of the controller and the controlled node, so different controllers do not affect each other. The designed protocol is verified on Freenet, and we conclude this paper with a detailed security analysis of the method to prove that the method satisfies forward security.